Cysticercosis included in the National One Health Strategic Plan for Kenya - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Kenya finalized its One Health Strategic Plan to guide one health prioritization in the country. Cysticercosis is now part of this due to evidence generated by A4NH researchers.